miRNA mediated mitochondrial function and gene regulation associated with Alzheimer’s disease - Subasinghe, Kumudu; Barber, Robert; Phillips, Nicole (Frontiers in Aging, 2025)
MicroRNAs (miRNAs) are small non-coding RNA molecules that are known to regulate gene expression in their target locations thereby contributing to epigenetic mechanisms associated with disease pathologies. Dysregulation of miRNA activity has been implicated in the pathology of Alzheimer’s disease (AD), offering insights into potential biomarkers for early diagnosis and therapeutic targets. Mitochondrial dysfunction and its associated effects (such as oxidative stress) can be seen in early-onset AD. This review critically examines recent findings on mitochondrial-associated miRNAs—including miR-34a, miR-140, miR-455-3p, and miR-1273g-3p—highlighting their roles in mitochondrial bioenergetics, oxidative stress, and synaptic function. We discuss the therapeutic potential of targeting specific miRNAs to restore mitochondrial health and explore their utility as early biomarkers for AD diagnosis. A better understanding of miRNA-mediated mitochondrial regulation may open new avenues for early intervention in AD.